2006
DOI: 10.1111/j.1365-2303.2006.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid rescreening of cervical smears as a quality control method in a high‐risk population

Abstract: Rapid review is beneficial as an internal quality assurance modality in an unscreened high-risk population and increases the detection of women with significant cervical lesions requiring treatment. The relatively low cost of rapid review compared with other rescreening modalities makes this an attractive option in low resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
10
0
5
Order By: Relevance
“…Also, 100% RR is supposed to have relatively low cost compared with other rescreening modalities, making it an attractive option for internal control in low-resource settings. 20 Our results confirm the qualities of 100% RR as a useful option for internal QC of cervical cytology diagnoses and to avoid false negative results. Further studies addressing costs should be performed to determine the cost-effectiveness of this quality control procedure in a public health cytology laboratory.…”
Section: Discussionsupporting
confidence: 75%
“…Also, 100% RR is supposed to have relatively low cost compared with other rescreening modalities, making it an attractive option for internal control in low-resource settings. 20 Our results confirm the qualities of 100% RR as a useful option for internal QC of cervical cytology diagnoses and to avoid false negative results. Further studies addressing costs should be performed to determine the cost-effectiveness of this quality control procedure in a public health cytology laboratory.…”
Section: Discussionsupporting
confidence: 75%
“…Michelow et al [30] reported that 16/19 (84.0%) cases identified at RR-100% were confirmed at repeat cytopathology and, even though our rates of agreement are lower, the result of repeat cytopathology confirmed 44.5% of cases identified at RPS and only 22.2% of cases identified at RR-100%. The studies by Lapin et al [24] and Alves et al [31] reported that 62.4 and 80.9% of cytopathology examinations, respectively, were abnormal on repeat cytopathology.…”
Section: Discussionmentioning
confidence: 66%
“…In the second, histopathology results were abnormal in 21% of cases of CIN1/+ and in 12% of cases of CIN2/+ [26,27]. The performance of RR-100% in the studies that took histopathology results into consideration ranged from 25 to 76.9% for CIN1/+ and 13.1 to 31.6% for CIN2/+ [14,28,29,30]. In this same study, an improvement was found in the performance of RS and consequently in the quality of the cytopathological diagnosis when the IQC methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the 1991 article by Baker and Melcher, at least an additional 37 articles have been published on some aspect of rapid rescreening of negative smears, reporting large or small studies, testing the best methods and times for rapid rescreening or editorializing 1, 3–41. Although the data have been variable, nearly all reports have concluded that additional abnormal cases have been detected at all levels beyond those found by 10% full rescreening of negatives, including high‐risk cases determined by a variety of clinical factors, most specifically a history of abnormal cervical cytology.…”
Section: Discussionmentioning
confidence: 99%